PET/CT-based adaptive radiotherapy of locally advanced non-small cell lung cancer in multicenter yDEGRO ARO 2017-01 cohort study - Mäurer, Matthias; Käsmann, Lukas; Fleischmann, Daniel F.; Oertel, Michael; Jazmati, Danny; Medenwald, Daniel (Radiation Oncology, 2022)
Background Stage III non-small cell lung cancer (NSCLC) represents a highly heterogeneous disease and treatment burden. Advances in imaging modality show promising results for radiotherapy planning. In this multicentric study, we evaluated the impact of PET/CT-based radiotherapy planning on the prognosis of patients with stage III NSCLC. Method and patients A retrospective observational cohort study (ARO 2017-01/NCT03055715) was conducted by the young DEGRO trial group of the German Society for Radiation Oncology (DEGRO) with the primary objective to assess the effect of tumour volume change during chemoradiotherapy and the secondary objective to assess the effect of treatment planning on survival. Three hundred forty-seven patients with stage III NSCLC treated at 21 university centers between January 2010 and December 2013 were enrolled in this trial. Patients received primary curative chemoradiotherapy with an intended dose of 50 Gy (hypofractionated) or > 60 Gy (normofractionated). To assess the effect of radiotherapy planning modality on overall survival, we used multivariate frailty models. Models were adjusted for gross tumor volume at the initiation of therapy, age, sex, simultaneous chemotherapy, lung comorbidities, RT dose and tumor grade. By considering the random effect, we can account for heterogeneity in survival and considered covariates within the model in relation to the study side. Results Patients were predominantly male (n = 269, 78.4%) with mainly adenocarcinoma (56.4%) and an average of 67.2 years. Adaptation of radiotherapy with consecutive reduction of irradiation volume showed no significant disadvantage for patient survival (HR = 1.21, 95% CI 0.89–1.64). The use of PET/CT co-registration in radiation planning tended to result in better oncologic outcomes, although no significant association could be shown (HR = 0.8, 95% CI 0.56–1.16). Centers with a consistent planning strategy performed better than those without a preferred planning method (0.62, 95% CI 0.41–0.94). Conclusion A consistent planning strategy has positive effects on overall survival. The use of PET/CT-based adaptive radiotherapy planning shows a similar survival prospect with the prospective of lower treatment volumes. In future research, toxicities need to be analysed in order to assess such reasoning.